Práticas docentes para sujeitos de ação: a contação de histórias pela estética da recepção no ensino fundamental I - Libardi, Franciele Lucia (2023)
In this research we introduce activities developed in educational practices regarding storytelling in action in Elementary School, as well as reflections and analyzes that involve them. Based on studies and our empirical knowledge on the theme, some questions emerge as guidelines for the investigation: We seek to cognize the ways in which storytelling, through the medium of a playful strategy of applying activities, reverberates in the reception of the researched students and if this pedagogical practice can be multiplied and influence the formation of other readers. With the purpose of finding answers to such problematization, we trace, as a general objective, to research about the oralization of stories through pedagogical practices with playful strategies of storytelling utilizing themes that provide analyzes about the socio-historical materiality of the students and possibilities of reflection on their affective confrontations that contribute to the strengthening of their self and literacy development. We support this study on the theoretical assumptions engendered by Freire (2019, 2020) regarding the concepts of democratic education; Iser (1996, 1999) and Jauss (1979, 1994) in relation to the perspective of the reception theory and the aesthetic effect. This is, therefore, a research based on the receptive method that considers Freirean arguments when it comes to the diagnosis of prior knowledge, the addition of knowledge and its resignification. Thus, data collection was possible by means of action research, with the operation of storytelling in a fifth year of Elementary School I, in a municipal public school located in Planalto, Paraná, Brazil. To this end, we applied a series of action activities to the sixteen enrolled students, utilizing the texts Marcelo, marmelo, martelo by Ruth Rocha (1976) and A pequena vendedora de fósforos by Hans Christian Andersen (1845), aiming at broadening their perceptions and readings of themselves, their realities and the world around them, through the reflections and productions carried out during the activities. As a result of such investigation process, we understand that literacy is an unfinished process that will last throughout the lives of students; however, at the hand of activities that promote their maturational performance and knowledge expansion about their socio-historical materiality, we can encourage reading development and contribute to personal and social development